Becoming Ted - Cain, Matt (Writer) (John Scognamiglio Books, Kensington Books, 2024)
"If Ted Ainsworth were to compare himself to one of the ice cream flavors made by his family's company, famous throughout his sleepy Lancashire hometown, it might be vanilla--sweet, inoffensive, and pleasantly predictable. At forty-three, Ted is convinced there's nothing remotely remarkable about him, except perhaps his luck in having landed handsome, charismatic Giles as a husband. Then Giles suddenly leaves him for another man, filling his social media feed with posts about #newlove and adventure. And Ted, who has spent nearly twenty years living with, and often for, another person, must reimagine the future he has happily taken for granted. But perhaps there is another Ted slowly blossoming now that he's no longer in Giles's shadow--funny, sassy, more uninhibited. Someone willing to take chances on new friendships, and even new love. Someone who's been waiting in the wings too long, but who's about to dust off a long-ago secret dream and overturn everyone's expectations of him--especially his own..."